Growth retardants in wheat and its effect in physiological quality of seeds - Souza,Leandro Torres de (2010)
Plant lodging in wheat has been controlled through growth retardants. However, there is lack of information on the effect of these products on the physiological quality of seeds. The objective of this study was to evaluate the physiological quality of wheat seeds obtained under different rates and application times of three growth retardants. The trial was carried out in Viçosa-MG, from May to September 2005, in a factorial and hierarchical scheme, in randomized block design with four replications and a control treatment. The treatments consisted of 500, 1000 and 1500g ha-1 of chlormequat; 40, 80 and 120g ha-1 of paclobutrazol and 62.5, 125 and 187.5g ha-1 of trinexapac-ethyl applied at the 6 or 8 growth stage based on the scale of Feeks and Large, and a control treatment without growth retardant application. Leaf application of growth retardants as chlormequat, paclobutrazol and trinexapac-ethyl did not affect the germination and vigor of wheat seeds.